Development of a highly sensitive glucose nanocomposite biosensor based on recombinant enzyme from corn. (3rd June 2022) - Izadyar, Anahita; Van, My Ni; Miranda, Marcela; Weatherford, Scout; Hood, Elizabeth E.; Seok, Ilwoo
Abstract: BACKGROUND: Enzymes are biocatalysts that play a vital role in the production of biomolecules. Plants can be a valuable and cost‐effective source for producing well‐structured recombinant enzymes. Glucose is one of the most important biological molecules, providing energy to most living systems. An electrochemical method for immobilization of enzyme is promising because it is economic, generates less component waste, improves the signal‐to‐noise ratio, leads to a lower limit of detection, and stabilizes and protects the enzyme structure. RESULTS: A glucose biosensor was constructed using polyaniline (PANI) and a recombinant enzyme from corn, plant‐produced manganese peroxidase (PPMP), with polymerization of aniline as a monomer in the presence of gold nanoparticles (AuNPs)‐glucose oxidase (GOx), and bovine serum albumin. Using linear sweep voltammetry and cyclic voltammetry techniques, PANI‐AuNPs‐GOx‐PPMP/Au electrode exhibited a superior sensing property with a wider linear range of 0.005–16.0 mm, and a lower detection limit of 0.001 mm compared to PANI‐GOx‐PPMP/Au electrode and PANI‐GOx‐PPMP/AuNPs/Au electrode. The biosensor selectivity was assessed by determining glucose concentrations in the presence of ascorbic acid, dopamine, aspartame, and caffeine. CONCLUSION: We conclude that a plant‐produced Mn peroxidase enzyme combined with conductive polymers and AuNPs results in a promising nanocomposite biosensor for detecting glucose. The use of such devices for quality control in the food industry can have a significant economic impact. © 2022 Society of Chemical Industry.